2011
DOI: 10.1016/j.mad.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte telomere length and physical ability among Danish Twins age 70+

Abstract: Leukocyte telomere length (LTL) shortens with age and is potentially a biomarker of human aging. We examined the relation of LTL with physical ability and cognitive function in 548 same-sex twins from the Longitudinal Study of Aging Danish Twins. LTL was measured by Southern blots of the terminal restriction fragments (TRF). Physical ability was evaluated using a self reported scale of 11 questions, while cognitive function was scored by MMSE and a cognitive composite score sensitive to age-related decline. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 48 publications
4
22
0
Order By: Relevance
“…The present cross-sectional analysis showed that the participants with longer LTL had a higher level of PA. A similar relationship between LTL and PA has been reported earlier in middle-aged and older subjects (Cherkas et al 2008;Bendix et al 2011). Many studies have, however, either failed to confirm this association (Harris et al 2006b;Cassidy et al 2010) or reported an inverted U-curve association in which telomeres were longest in participants who were moderately active and shortest among those who were inactive or very active (Ludlow et al 2008).…”
Section: Discussionsupporting
confidence: 88%
“…The present cross-sectional analysis showed that the participants with longer LTL had a higher level of PA. A similar relationship between LTL and PA has been reported earlier in middle-aged and older subjects (Cherkas et al 2008;Bendix et al 2011). Many studies have, however, either failed to confirm this association (Harris et al 2006b;Cassidy et al 2010) or reported an inverted U-curve association in which telomeres were longest in participants who were moderately active and shortest among those who were inactive or very active (Ludlow et al 2008).…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have found no correlation between LTL and cognitive function (Harris et al, 2006; Bendix et al, 2011, 2014a; Cohen-Manheim et al, 2016). Furthermore, two cohort studies have found that short LTL predicts cognitive decline (Martin-Ruiz et al, 2006; Yaffe et al, 2011).…”
Section: Introductionmentioning
confidence: 85%
“…LTL has been shown to be associated with mortality (3,4), perceived age (5) and physical ability (6).…”
Section: Introductionmentioning
confidence: 99%